Sustainable progression of technology education for atomic energy engineering in tsuyama national college of technology - Toshiro KOBAYASHI (The Japan Society of Mechanical Engineers, 2014)
This study describes the achievements of a program that provides technology education about radiation to develop practical core engineers, then the effects of the programed were discussed. An education program starting at an early age and continuous and consistent educational agendas through seven years of college has been constructed in collaboration with regional organizations. Subjects relating to atomic energy or nuclear engineering were regrouped as “Subjects Related to Atomic Power Education” for most grades in each department. These subjects were included in the syllabus and the student guide book to emphasize a continuous and consistent policy throughout the seven-year period of college study, comprising the five-year system and the additional two-year advanced course. Furthermore, the content of lectures, experiments, and internships was enriched and realigned in collaboration with the Japan Atomic Energy Agency (JAEA), Okayama University, and Chugoku Electric Power Co., Inc. Additional educational materials were developed from inspection visits by teaching staff to atomic energy facilities were also used in the classes. Two student experiment textbooks were developed to promote two of the subjects related to atomic energy: “Cloud Chamber Experiment” and “A Test of γ-ray Inverse Square Law.” In addition to the expansion and rearrangement of atomic power education, research on atomic power conducted for graduation thesis projects was undertaken to enhance educational and research activities. Some examples are as follows: “Study on the Relation between γ Dose Rate and Rainfall in Northern Okayama Area,” “Remote Sensing of Radiation Dose Rate by Customizing an Autonomous Robot,” and “Nuclear Reaction Analysis for Composition Measurement of BN Thin Films.” It should be noted that an atomic-energy-related education working group has been in place officially to continue the above activities in the college since 2011. In consequence, although government subsidy has been decreasing, both human and material resources have been enhanced, and many students with a satisfactory understanding of atomic energy are being developed.